Assistive devices, hip precautions, environmental modifications and training to prevent dislocation and improve function after hip arthroplasty (Review) - Smith, Toby O.; Jepson, Paul; Beswick, Andrew; Sands, Gina; Drummond, Avril E.R.; Davis, Edward T.; Sackley, Catherine Mary (Wiley, 2016)
Background: Total hip arthroplasty (THA) is one of the most common orthopaedic operations performed worldwide. Painful osteoarthritis of the hip is the primary indication for THA. Following THA, people have conventionally been provided with equipment, such as raised toilet seats and chairs, and educated to avoid activities that could cause the hip joint to be in a position of flexion over 90 degrees, or adduction or rotation past the midline. These aspects of occupational therapy have been advocated to reduce the risks of prosthesis dislocation. However, the appropriateness of these recommendations has been questioned.